2021
DOI: 10.5435/jaaosglobal-d-21-00165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sports Medicine Fellowships in the United States Based on Academic Productivity

Abstract: Background: Institutional academic productivity remains an influential factor in an applicant's selection of fellowship training. This study aimed to determine the quality and quantity of research in the United States orthopaedic sports medicine fellowship programs and identify those with highest productivity. Methods: The Arthroscopy Association of North America Fellowship Directory was used to evaluate 88 fellowships in the United States. Publication data and Hirschberg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Mayfield et al. 24 sought to rank orthopaedic sports medicine fellowships in the United States based on academic productivity. The authors found the top-5 programs to be (1) HSS, (2) RUMC, (3) University of Pittsburgh Medical Center (UPMC), (4) Mayo Clinic (Rochester), and (5) Boston Children’s Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Mayfield et al. 24 sought to rank orthopaedic sports medicine fellowships in the United States based on academic productivity. The authors found the top-5 programs to be (1) HSS, (2) RUMC, (3) University of Pittsburgh Medical Center (UPMC), (4) Mayo Clinic (Rochester), and (5) Boston Children’s Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, orthopaedic surgery residencies have been altered by increased work-hour restrictions and operative supervision, and therefore the vast majority of residents participate in a postgraduate fellowship year to enhance their technical skills and experience. 1 Thus, COVID-19erelated operating room shutdowns were a specific concern for orthopaedic fellowship training programs, as these are only 1 year in length and the class of 2019-2020 was only two-thirds of the way through their program when the pandemic began. Orthopaedic sports medicine is a field with a particularly high elective caseload and had potential to be markedly affected by the canceling of elective cases.…”
mentioning
confidence: 99%